2015
DOI: 10.1186/s12909-015-0459-2
|View full text |Cite
|
Sign up to set email alerts
|

A typology of uncertainty derived from an analysis of critical incidents in medical residents: A mixed methods study

Abstract: BackgroundMedical uncertainty is inherently related to the practice of the physician and generally affects his or her patient care, job satisfaction, continuing education, as well as the overall goals of the health care system. In this paper, some new types of uncertainty, which extend existing typologies, are identified and the contexts and strategies to deal with them are studied.MethodsWe carried out a mixed-methods study, consisting of a qualitative and a quantitative phase. For the qualitative study, 128 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 26 publications
(39 reference statements)
1
63
0
Order By: Relevance
“…According to the literature, optimal role-modelling means explicitly setting the rules about how hierarchical relationships operate in different environments and how trainees should expect to be embedded within them ( CMOC 14 in Part S5). 28 , 50 , 53 , 55 , 61 , 83 , 97 , 101–109 Conversely, role-modelling may result in the reinforcement of suboptimal prescribing habits and prescribing etiquette(s) if rules remain implicit or are only enforced through authority and the rationale is not clarified to facilitate learning ( CMOC 15 in Part S5). 27 , 28 , 50 , 53–55 , 64 , 77 , 84 , 97 , 109–113 Such hierarchical environments where the rationale for prescribing decisions is rarely discussed are often perceived to contribute to a culture of using doctors-in-training to provide service rather than prioritizing their learning needs ( CMOC 16 in Part S5).…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, optimal role-modelling means explicitly setting the rules about how hierarchical relationships operate in different environments and how trainees should expect to be embedded within them ( CMOC 14 in Part S5). 28 , 50 , 53 , 55 , 61 , 83 , 97 , 101–109 Conversely, role-modelling may result in the reinforcement of suboptimal prescribing habits and prescribing etiquette(s) if rules remain implicit or are only enforced through authority and the rationale is not clarified to facilitate learning ( CMOC 15 in Part S5). 27 , 28 , 50 , 53–55 , 64 , 77 , 84 , 97 , 109–113 Such hierarchical environments where the rationale for prescribing decisions is rarely discussed are often perceived to contribute to a culture of using doctors-in-training to provide service rather than prioritizing their learning needs ( CMOC 16 in Part S5).…”
Section: Resultsmentioning
confidence: 99%
“…In his model, Beresford distinguished three issues of uncertainty, which he suggested affect decision‐making: technical uncertainty (ie, indeterminate data); conceptual uncertainty (ie, the misalignment between abstract criteria and real‐world problems); and personal uncertainty (ie, inadequate understanding of patient wishes) . Beresford's model was applied as a framework for subsequent studies . For example, in 2008, Farnan and colleagues investigated the experiences of uncertainty among medical residents, further qualifying the domains of Beresford's model to include transitions of care, diagnostic decision‐making, and management conflict (conceptual); procedural skills and knowledge of indications (technical); and goals of care (personal).…”
Section: Previous Taxonomies Of Uncertaintymentioning
confidence: 99%
“…For example, in 2008, Farnan and colleagues investigated the experiences of uncertainty among medical residents, further qualifying the domains of Beresford's model to include transitions of care, diagnostic decision‐making, and management conflict (conceptual); procedural skills and knowledge of indications (technical); and goals of care (personal). In 2015, a mixed‐method study by Hamui‐Sutton and colleagues further developed Beresford's model to include five types of uncertainty, adding systematic and ethical uncertainty to technical, conceptual, and communication uncertainty (personal uncertainty in Beresford's work). Despite Beresford's early efforts to take into account a variety of healthcare settings, empirical work extending his model has been limited to the perspectives of medical residents .…”
Section: Previous Taxonomies Of Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, medical trainees resolve medical uncertainty by consulting seniors through a predetermined hierarchy [ 39 ]. Farnan et al [ 2 ] reported that residents had managed uncertainty in critical incidents through a firm hierarchy, seeking help from colleagues and literature first, and then senior residents, specialty fellows, and the attending physician.…”
Section: Tolerance/intolerance Of Medical Uncertaintymentioning
confidence: 99%